"Don't Reject Me:" Directed and Non-Directed Living Organ Donor Narratives and the Construction of the Organ Donation and Transplantation Process as a Meaningful Experience. - Boychuk, Martina (My University, 2010)
The organ donation and transplantation process is a highly emotional experience for directed and non-directed living organ donors. However, both types of living organ donors construct the process as a meaningful experience because, through the act of offering a kidney for donation, they help to extend the lives of those diagnosed with end-stage renal failure.
I argue that directed and non-directed living organ donors are active participants in the organ donation and transplantation process while they are patients of the Ottawa Hospital Renal Transplant Clinic. Moreover, through negotiation and, at times, social manipUlation, directed living organ donors and their family members, include or exclude others as potential donor candidates.
p.p1 {margin: 0.0px 0.0px 0.0px 0.0px; font: 11.5px Times}
The Ottawa Hospital Renal Transplant Clinic refers to the organ donation and
transplantation process as giving the "gift of life." However, my research on directed
living organ donor narratives suggest that donors construct the kidney as a reciprocal gift,
analogous to gifts given at Christmas or anniversaries. Furthermore, the directed living
organ donor narratives suggests that through naming, gendering and imbuing the kidney
with personality traits reflective of the donor, the kidney is understood to be an extension
of the donor's self.
Keywords: Anthropology; Anthropology